Improved analysis of ultra‐high molecular mass polystyrenes in matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry using DCTB matrix and caesium salts. (20th April 2015) - Gabriel, S. J.; Steinhoff, R. F.; Pabst, M.; Schwarzinger, C.; Zenobi, R.; Panne, U.; Weidner, S. M.
Abstract : Rationale: The ionization of polystyrenes in matrix‐assisted laser desorption/ionization mass spectrometry (MALDI‐MS) is typically achieved by the use of silver salts. Since silver salts can cause severe problems, such as cluster formation, fragmentation of polymer chains and end group cleavage, their substitution by alkali salts is highly desirable. Methods: The influence of various cations (Ag +, Cs + and Rb + ) on the MALDI process of polystyrene (PS) mixtures and high mass polystyrenes was examined. The sample preparation was kept as straightforward as possible. Consequently, no recrystallization or other cleaning procedures were applied. Results: The investigation of a polystyrene mixture showed that higher molecular polystyrenes could be more easily ionized using caesium, rather than rubidium or silver salts. In combination with the use of DCTB as matrix a high‐mass polymer analysis could be achieved, which was demonstrated by the detection of a 1.1 MDa PS. Conclusions: A fast, simple and robust MALDI sample preparation method for the analysis of ultra‐high molecular weight polystyrenes based on the use of DCTB and caesium salts has been presented. The suitability of the presented method has been validated by using different mass spectrometers and detectors. Copyright © 2015 John Wiley & Sons, Ltd.